PARTISIPASI POLITIK NU DAN KADER MUSLIMAT DALAM LINTAS SEJARAH - Munawir Haris (IAIN Ponorogo, 2015)
Abstract: Political movement of Nahdhatul Ulama’ (NU) as a religious organization and NU Women Cadre (Muslimat NU) as an autonomous body appeared in the trajectory of the national history. The problem that arised was that to what the extent NU had participated in national politics and how big Muslimat NU’s representation was in national politics. Through a typology approach, this article explored the political contributions of NU and NU Women Cadre in the trajectory of the national history. A lot of data indicated that NU and muslimat NU had taken part both passively and actively in national politics. In the colonial era, typologically NU took part as passive participant, but in the next period, it took part in the form of non-conventional active participants.This active participant apparently showed its participation when NU issued Jihad Resolution to defend Indonesian independence. Its participation was then allied with Masjumi, but then it built its own political party independently. The passive participation of NU Women Cadres (Muslimat) began to be recognized in 1938, and then it just began to be recognized as active participant in 1946. Women of NU became active participants to promote gender equality in 1954. Five years later, it became galdiator participant, and began to show its gender roles simultaneously by raising the strategic issues aimed at enforcing the rights, resources of human being and aspirations for women to participate in public life, including practical politics.الملخص :ظهرت الحركة السياسية لنهضة العلماء كجمعية دينية والمنظمة التابعة لها